Evaluation of the feasibility of posting reduced speed limits on Kansas gravel roads - Liu, Litao (Kansas State University, 2008)
In the United States, the mileage of unpaved roads is about 1.6 million miles. Total length of unpaved roads in Kansas is about 98,000 miles, of which about 78,000 miles are gravel roads. Most of the gravel roads are not posted with speed limit signs but regulated with a 55 mph blanket speed limit established by the Kansas Statutes. Surface conditions of gravel roads are very likely to change with time, space, and quality of maintenance work, making it even more necessary to have proper control of speeds on gravel roads. Normally used speed regulations and rules for freeways or other types of paved roadways might not be appropriate for gravel roads, especially for those local gravel roads which usually carry very low traffic in rural areas. Based on an extensive literature search, there was no specific rule or references to provide guidelines on how speed limits on gravel roads could be set. Therefore, an effort was made in this study to evaluate the effects of currently posted lower speed limits in some counties in Kansas, based on traffic characteristics and safety on gravel roads, with the intention of providing proper guidelines for setting speed limits on gravel roads in Kansas. In order to study traffic characteristics on gravel roads, field speed studies were conducted with automatic traffic counters on more than forty gravel road sections in seven counties in Kansas. Important speed measures, such as 85th-percentile speed and mean speed, were obtained from the raw data. A group of other related road characteristics were also recorded at the time of field data collection. Crash data on gravel roads were extracted from the Kansas Accident Recording System (KARS) database. Speed analysis on a number of gravel roads where the statutory imposed, unposted speed limit of 55 mph was utilized indicated that they are functioning at a reasonably acceptable level in terms of actual speeds. In order to evaluate whether there were differences in traffic speeds between two counties or groups which have different speed limit settings on gravel roads, t-test was used. The analysis found that there was no significant difference between the mean speeds in two counties, one of which has 35 mph posted speed limit on gravel roads while the other does not post any speed limits. Moreover, the mean speed on the sections with 35 mph posted speed was a little higher than that on gravel roads without any speed limits. Linear models to predict 85th-percentile speed and mean speed on gravel roads were developed based on speed data. Both models indicated that traffic speeds are not significantly affected by the speed limit, but are related with 90% confidence to road width, surface classification and percentage of large vehicles in traffic. Chi-square tests were conducted with the crash data, and the results indicated that the posted 35 mph speed limit on gravel roads had not resulted in either smaller total number of crashes or decreased proportion of severe crashes, compared to gravel roads where no speed limits were posted. Logistic regression models were also developed on four levels of crash severity, which indicated that gravel roads with higher speed limits are likely to experience higher probability of having injury crashes. Two mail-back surveys were also conducted to gather the opinions of county engineers and road users on the subject of suitable speed limits on gravel roads. The majority of county engineers believed that blanket speed limit should be used for gravel roads and does not need to be posted. Three restrictions: changeful road conditions, unpractical law enforcement, and limited funds, are basic reasons why they do not think that gravel roads should be posted. Besides that, a few respondents said 55 mph is too high for gravel roads and needs to be lowered. Majority of the road users suggested that all gravel roads be posted with lower speed limit signs. However, they were more concerned about law enforcement since they believe that posted speeds won't bring any benefits if no law enforcement patrol gravel roads. Based on all aspects looked into in this study, it does not appear that reducing the speed limits and posting it with signs, is going to improve either traffic operational or safety characteristics on gravel roads in Kansas, and therefore is not recommended for new situations.
Keywords: Gravel Road; Speed Limit; Engineering, Civil (0543)